1992
DOI: 10.1080/14640749208401326
|View full text |Cite
|
Sign up to set email alerts
|

On the Relation between Time Perception and the Timing of Motor Action: Evidence for a Temporal Oscillator Controlling the Timing of Movement

Abstract: Studies of time estimation have provided evidence that human time perception is determined by an internal clock containing a temporal oscillator and have also provided estimates of the frequency of this oscillator (Treisman, Faulkner, Naish, & Brogan, 1990; Treisman & Brogan, 1992). These estimates were based on the observation that when the intervals to be estimated are accompanied by auditory clicks that recur at certain critical rates, perturbations in time estimation occur. To test the hypothesis that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
2
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(76 citation statements)
references
References 55 publications
5
67
2
2
Order By: Relevance
“…Gruber and Block (2003) also reported that their effects of caffeine on timing cannot be explained easily by recourse to a single timer, since caffeine only affected performance when estimates were requested prospectively, not when requested retrospectively. Relatedly, in the present series of experiments, the selectivity of caffeine's effects for reaction time performance rather than for time production or discrimination seems inconsistent with the idea that time estimation and reaction time are based on a single (or, at least, common) oscillator (e.g., Treisman et al 1992). If that were the case, the two kinds of task would be expected to exhibit similar changes under the influence of caffeine.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Gruber and Block (2003) also reported that their effects of caffeine on timing cannot be explained easily by recourse to a single timer, since caffeine only affected performance when estimates were requested prospectively, not when requested retrospectively. Relatedly, in the present series of experiments, the selectivity of caffeine's effects for reaction time performance rather than for time production or discrimination seems inconsistent with the idea that time estimation and reaction time are based on a single (or, at least, common) oscillator (e.g., Treisman et al 1992). If that were the case, the two kinds of task would be expected to exhibit similar changes under the influence of caffeine.…”
Section: Discussioncontrasting
confidence: 87%
“…If that were the case, the two kinds of task would be expected to exhibit similar changes under the influence of caffeine. Treisman et al (1992) based their claim of a common oscillator on two experiments with a small number of different subjects in which performance was impaired by a concurrent auditory click sequence. They claimed that this impairment only occurred when the click rate was at certain frequencies and that the frequencies matched in the two experiments.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a mental rotation task (Cooper & Shepard, 1973) should interfere with visuospatial processes (e.g., CME) that potentially occur in the PM task and thereby affect concurrent TIC judgments (Liddell, 1998). This is a reasonable proposal especially because previous results suggest that both time perception and motor action use the same or similar timing mechanisms (Treisman et al, 1992) and that visuospatial processing in working memory can interfere with concurrent time estimation (Fortin & Breton, 1995).…”
Section: Summary and General Discussionmentioning
confidence: 99%
“…Indeed, previous results suggest that both time perception and motor action use the same or similar timing mechanisms (Treisman, Faulkner, & Naish, 1992). Nevertheless, an assumption that the same clocking process is used in PM tasks and time perception does not solve the problem of designing an interference task because there are several models of time estimation (for a review, see Block, 1990).…”
Section: Application Of Selective Interference To a Pm Taskmentioning
confidence: 99%
“…; A200V: t(15) = 0.05, n.s. ; V200A: t(15) = 1.7, n.s.. et al, 1990, 1992): specifically, external temporal regularities can impose modulations of the pacemaker frequency so as to entrain the internal clock (Treisman et al, 1992). Similarly, intrinsic neural oscillations match the temporal scales of perceptual phenomena (Buzsáki and Draguhn, 2004;Roopun et al, 2008;van Wassenhove, 2009;Wang, 2010) and can be entrained to external rhythms (Rees et al, 1986;Regan, 1966).…”
Section: Neural Oscillations As Pacemakers For the Encoding Of Timementioning
confidence: 99%